Pendampingan Pengembangan Organisasi BUMDes Desa Gedongmulyo Kecamatan Lasem, Kabupaten Rembang Menuju Sustainable Institution - Mochamad Rizki Fitrianto; Amni Zarkasyi Rahman; Juang Abdi Muhammad; Satria Aji Imawan; Maesaroh; Dyah Lituhayu (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2025)
Village-Owned Enterprises (BUMDes) serve as an essential instrument in promoting rural economic independence through the management of local potential. Gedongmulyo Village, located in Lasem District, Rembang Regency, possesses significant coastal resources; however, these have not yet been fully optimized by the BUMDes. This community service activity aims to strengthen the institutional capacity of BUMDes toward a sustainable institution through human resource development, creative business innovation, expansion of collaborative networks, and enhancement of community participation. The implementation method employed a participatory approach through training, mentoring, and business network facilitation. The results indicate an improvement in the managerial competence of BUMDes administrators, diversification of processed marine products, expansion of partnerships with local entrepreneurs, and increased community trust in BUMDes management. This activity demonstrates that strengthening the four key pillars of human resources, business diversification, collaboration, and community participation constitutes a fundamental foundation for developing a sustainable and independent BUMDes